(untitled) (Zien Journal of Social Sciences and Humanities, 2022)
In the article, competence is the ability of a specialist to work effectively based on existing knowledge, skills and qualifications, today the professional competence of a specialist is becoming more relevant as a factor guaranteeing the quality and efficiency of the activities organized by him, professional competence is mastered by a specialist to be able to use knowledge, acquired skills, and experience in the process of organizing activities without any difficulty or strain, and the main focus is on revealing the essence of the concepts of "professional-graphic competence", "professional-graphic competence", In general, the essence of the concepts of "competence", "competence", and "professional-graphic competence" from a specific point of view, the qualities of professional-graphic competence and their description, it is shown that the possession of the qualities of professional-graphic competence is an important factor in increasing the effectiveness of activities in modern conditions..